Anxiety, Uncertainty, and Resilience During the Pandemic Period - Anthropological and Psychological Perspectives 2021
DOI: 10.5772/intechopen.97863
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anxiety Disorders and Protective-Risk Factors in Children during Pandemic Process

Abstract: In this study, the possible negative effects of the pandemic process on children with anxiety disorders or anxiety sensitivity, risk factors and protective factors are discussed from a psychological point of view. In this context, were tried to review risk factors and protective factors by compiling the studies published in the literature on behavioral and emotional disorders observed in children, especially during the pandemic period. As risk factors are discussed mainly personal psychological characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, as several studies have demonstrated, part of the reality is that students experiencing ACEs may rely in part on teachers for initial discussion of their situation which may tend to place teachers in a de facto assistive role to the mental health professionals for initial screening and even observation as students are in class regularly [45,50]. This is more support for the calls to increase collaboration between K-12 school administrators, school mental health professionals, teachers, and students' families [49,57,83]. The students' microsystems, mesosystems, and exosystems are intrinsically linked, and so the importance of collaboration is essential in addressing psychic contagion, especially from a semantic perspective.…”
Section: When Emotional Intelligence As Labor Is Semantically Linked ...mentioning
confidence: 99%
“…Nevertheless, as several studies have demonstrated, part of the reality is that students experiencing ACEs may rely in part on teachers for initial discussion of their situation which may tend to place teachers in a de facto assistive role to the mental health professionals for initial screening and even observation as students are in class regularly [45,50]. This is more support for the calls to increase collaboration between K-12 school administrators, school mental health professionals, teachers, and students' families [49,57,83]. The students' microsystems, mesosystems, and exosystems are intrinsically linked, and so the importance of collaboration is essential in addressing psychic contagion, especially from a semantic perspective.…”
Section: When Emotional Intelligence As Labor Is Semantically Linked ...mentioning
confidence: 99%